Menyoal Batas Usia Pernikahan di Indonesia Perspektif Pemikiran Alie Yafie - Ahmat Saiful (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
after the equal marriage age was established through Law No. 16 of 2019. In Islam, there is no specific regulation regarding the age limit for marriage. This research explores Alie Yafie's thoughts on Indonesia's marriage age limit. The study is qualitative, using a library research approach. Primary data comes from Alie Yafie’s book Initiating Social Fiqh, while secondary data is derived from journals discussing marriage age limits and maslahah in Yafie’s thought, along with other supporting literature. Data collection was done through document analysis related to the marriage age limit and the concept of maslahah. The data was analyzed using content analysis. The findings reveal that Indonesia's high rate of child marriage is a significant issue, with marriages below 19 years being prone to divorce due to psychological and economic unpreparedness. Alie Yafie supports the government's decision to set the marriage age limit at 19 years, rooted in the maslahah concept to enhance family welfare.